Antifungal activity of flavonoids from Heteropterys byrsonimifolia and a commercial source against Aspergillus ochraceus: In silico interactions of these compounds with a protein kinase - Santos Junior, Helvecio M.; Campos, Viviane A. C.; Alves, Dejane S.; Cavalheiro, Alberto José [UNESP]; Souza, Luciana P.; Botelho, Deila M. S.; Chalfoun, Sara M.; Oliveira, Denilson F. (Elsevier B.V., 2014)
To contribute to the development of new methods to reduce the contamination of coffee beans with Aspergillus ochraceus and ochratoxin A, a toxin produced by this fungus, the present work initially aimed to select plant extracts active against A. ochraceus. Among the extracts from 43 plant species, the most active was the one obtained from leaves of Heteropterys byrsonimifolia. This extract was subjected to a fractionation process that resulted in the purification of four flavonoids, among which the most active against the fungus was rutin, which presented a minimal inhibitory concentration (MIC, 32.5 mu g/mL) close to the value obtained for the commercial fungicide benzalkonium chloride (7.84 mu g/mL). In vitro studies with the isolated flavonoids and other four from commercial sources showed that the MIC for the flavonoid chrysin is equal to that observed for rutin, and results from an in silico study suggested that these flavonoids act against A. ochraceus by binding to a protein kinase produced by this fungus. Consequently, this enzyme and the studied flavonoids are potentially useful for the development of new products to control A. ochraceus in coffee beans. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Fungicide; Rutin; Coffea arabica; Computer simulation; Methanolic extract